Fossil extraction bans and carbon taxes: Assessing their interplay through multiple models - Pietro Andreoni; Lara Aleluia Reis; Laurent Drouet; Olivier Dessens; Panagiotis Fragkos; Robert Pietzcker; Steve Pye; Renato Rodrigues; Massimo Tavoni (iScience, 2023)
Summary: Given concerns about the ambition and effectiveness of current climate policies, a case has been made for the combination of demand side policies such as carbon pricing with supply side bans on fossil fuel extraction. However, little is known about their interplay in the context of climate stabilization strategies. Here, we present a multi-model assessment quantifying the effectiveness of supply side policies and their interactions with demand-side ones. We explore a variety of fossil fuel bans with four integrated assessment models and find that international supply side policies reduce carbon emissions but not at sufficient levels to stabilize temperature increase to well below 2°C. When combined with demand side policies, supply side policies reduce the required carbon price, dampen reliance on CO2 removal technologies, and increase investment in renewable energy. The results indicate the opportunity to integrate fossil fuel bans alongside price-based policies when exploring pathways to reach ambitious mitigation targets.